2011
DOI: 10.1111/j.1601-183x.2011.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

A reversal learning task detects cognitive deficits in a Dachshund model of late-infantile neuronal ceroid lipofuscinosis

Abstract: The neuronal ceroid lipofuscinoses (NCLs) are autosomal recessive lysosomal storage diseases characterized by progressive neurodegeneration and by accumulation of autofluorescent storage material in the central nervous system and other tissues. One of the most prominent clinical signs of NCL is progressive decline in cognitive function. We previously described a frame shift mutation of TPP1 in miniature long-haired Dachshunds which causes an early-onset form of NCL analogous to classical late-infantile onset N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…The TPP1-null dachshund disease model has a frameshift mutation in TPP1 (17) with no detectable TPP1 protein or activity in blood or tissues and progressive neurodegenerative symptomatology that recapitulates human TPP1 deficiency (18, 19). First, we tested whether rAAV transduction of ependyma with TPP1 can provide widespread access of recombinant TPP1 to the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…The TPP1-null dachshund disease model has a frameshift mutation in TPP1 (17) with no detectable TPP1 protein or activity in blood or tissues and progressive neurodegenerative symptomatology that recapitulates human TPP1 deficiency (18, 19). First, we tested whether rAAV transduction of ependyma with TPP1 can provide widespread access of recombinant TPP1 to the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…84 This model system is particularly interesting because intrathecal administration of TTP1 results in decreased lysosomal storage. 85 It is likely that a better understanding of how mitochondrial dysfunction and neuronal loss develop in the NCLs, as well as how they may be reversed with therapy, will shed light on similar mechanisms postulated to occur in brain aging.…”
Section: Neurobiology Of Aging In the Dogmentioning
confidence: 99%
“…Affected animals display progressive neurological decline requiring euthanasia at 10-11 months old [15,26]. We have previously demonstrated that repeat intrathecal (IT) injection results in brain distribution of active rhTPP1 and reduced accumulation of lysosomal storage [32].…”
Section: Introductionmentioning
confidence: 98%